Islamic Education in the Timeline: Transformation of Islamic Religious Education Material through Social Media - Misrida, Anisa; Walidin, Warul; Salami; Fatmawati (Universitas Islam Negeri Raden Intan Lampung, 2026)
The development of social media has brought significant changes to educational practices, including the delivery of Islamic Religious Education (IRE) materials. Social media is no longer merely a means of communication, but has evolved into an alternative space that facilitates the distribution, reinterpretation, and reproduction of IRE materials in the digital realm. This article aims to analyze how Islamic Religious Education materials undergo transformation when produced and disseminated through social media timelines. This study uses a qualitative approach with a literature review, through a systematic review of literature relevant to Islamic education and digital media. The results of the study show that this transformation is evident in changes to the form and format of PAI material, which tends to be more concise, visual, contextual, and responsive to current issues. In addition, social media also influences the pattern of material production, in which not only formal educational institutions play a role, but also digital actors who present PAI material in various styles of communication. This transformation expands access to religious learning, but at the same time presents pedagogical challenges in the form of material fragmentation and the potential simplification of teaching substance. These findings confirm that social media has shaped a new landscape for Islamic education in the digital age. Therefore, it is necessary to strengthen digital and religious literacy so that the transformation of Islamic Education material in the timeline remains in line with pedagogical principles and systematic Islamic scientific traditions.